Surviving septic patients endotyped with a functional assay demonstrate active immune responses - Price, Adam D.; Becker, Ellen R.; Barrios, Evan L.; Mazer, Monty B.; McGonagill, Patrick W.; Bergmann, Christian B.; Goodman, Michael D.; Gould, Robert W.; Rao, Mahil; Polcz, Valerie E.; Kucaba, Tamara A.; Walton, Andrew H.; et al. (Frontiers in Immunology, 2024)
Sepsis is a complex clinical syndrome characterized by a heterogenous host immune response. Historically, static protein and transcriptomic metrics have been employed to describe the underlying biology. Here, we tested the hypothesis that ex vivo functional TNF expression as well as an immunologic endotype based on both IFNγ and TNF expression could be used to model clinical outcomes in sepsis patients.Methods: This prospective, observational study of patient samples collected from the SPIES consortium included patients at five health systems enrolled over 17 months, with 46 healthy control patients, 68 ICU patients without sepsis, and 107 ICU patients with sepsis. Whole blood was collected on day 1, 4, and 7 of ICU admission. Outcomes included in-hospital and 180-day mortality and non-favorable discharge disposition defined by skilled nursing facility, long-term acute care facility, or hospice. Whole blood ELISpot assays were conducted to quantify TNF expression (stimulated by lipopolysaccharide (LPS)) and IFNγ expression (stimulated by anti-CD3/CD28 mAb), which were then used for assignment to one of four subgroups including an 'immunocompetent', 'immunosuppressed endotype', and two 'mixed' endotypes.Results: Whole blood TNF spot-forming units were significantly increased in septic and CINS patients on days 4 and 7 compared to healthy subjects. In contrast, TNF expression per cell on days 1, 4, and 7 was significantly lower in both septic and critically ill non-septic (CINS) patients compared to healthy subjects. Early increases in total TNF expression were associated with favorable discharge disposition and lower in-hospital mortality. 'Immunocompetent' endotype patients on day 1 had a higher proportion of favorable to non-favorable discharges compared to the 'immunosuppressed' endotype. Similarly, 'immunocompetent' endotype patients on day 4 had a higher in-hospital survival compared to the 'immunosuppressed' endotype patients. Finally, among septic patients, decreased total TNF and IFNγ expression were associated with 180-day mortality.Conclusions: Increased ex vivo whole blood TNF expression is associated with improved clinical outcomes. Further, the early 'immunocompetent' endotype is associated with favorable